Short Communication Nutrient and Antinutrient Contents of Fermented Roselle Calyx (Biological Sciences - PJSIR, 2006)
Pure strains of Aspergillus niger, Aspergillus flavus, Saccharomyces cereviciae and Bacillus subtilis were isolated, cultured and subsequently used to ferment four portions of 100 g each of roselle calyx for 72 h. A decrease in pH with an increase in total titratable acidity (TTA) was recorded. The results of the proximate analysis revealed a significant increase in the protein content of the fermented calyx samples (10.8 ± 1.1 - 12.6 ± 1.1) compared with the unfermented (4.8 ± 1.3). There was no significant increase in the fat content while there was a significant decrease in the ash content. There was a significant decrease (P < 0.05) in the antinutrient content (phytate from 2143.6 ± 0.8 mg/100 g in the unfermented sample to 488.8 ± 3.7 mg/100 g and tannin from 5.30 ± 1.1% in the unfermented sample to 1.32 ± 0.1%) after 72 h of fermentation.